1992
DOI: 10.2134/jpa1992.0532
|View full text |Cite
|
Sign up to set email alerts
|

Concept for Monitoring the Growth and Development of Cotton Plants Using Main-Stem Node Counts

Abstract: Management efficiency in cotton (Gossypium hirsutum L.) can be improved by implementing strategles that may be adjusted in response to expected or realized changes in plant growth and development. We propose that successive counts of main‐stem nodes bearing sympodia with a preflower fruiting structure in the first position are practical, dynamic measurements of plant development. A technique of monitoring number of main‐stem nodes above the sympodial branch bearing a white flower in the first position from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 8 publications
3
82
1
2
Order By: Relevance
“…Nodal development of cotton was evaluated using nodes above squaring node and nodes about white flower as estimates of crop [16] Similar to petiole NO À 3 -N analyses, node development was only occasionally significantly affected by N treatments in 1995 (data not shown). More significant differences were observed from 1996 to 1998 (Tables 7-10).…”
Section: Node Developmentmentioning
confidence: 93%
See 1 more Smart Citation
“…Nodal development of cotton was evaluated using nodes above squaring node and nodes about white flower as estimates of crop [16] Similar to petiole NO À 3 -N analyses, node development was only occasionally significantly affected by N treatments in 1995 (data not shown). More significant differences were observed from 1996 to 1998 (Tables 7-10).…”
Section: Node Developmentmentioning
confidence: 93%
“…Data collected from these studies included lint yield, plant height, and soil NO À 3 -N. Additionally, nodal development [16] and petiole NO À 3 -N concentration [17] were evaluated weekly through the growing season. Data were analyzed using the Statistical Analysis System (SAS Institute, Inc., Cary, NC, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Farmers (or consultants) often use the stage of cotton plant growth and development to time the application of inputs such as irrigation water, plant growth regulators, pesticides and harvest aids (i.e. defoliants and or desiccants to prepare the crop for harvest) (Bourland et al 1992). Thus, RS may have great potential in cotton production because imagery can be obtained at regular intervals during the growing season and can be related to current crop status.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists with the University of Arkansas have developed a procedure based on the vertical position of the uppermost white ßower along the cotton plantÕs main stem to estimate plant maturity consistently (Bourland et al 1992). Additional research has shown that the Þnal boll population contributing to yield is present on plants when the uppermost white ßower occurs within Þve main stem nodes of the plant terminal (Bernhardt et al 1986, Bagwell 1994.…”
Section: Discussionmentioning
confidence: 99%